An interdisciplinary periodontic-orthodontic approach to the treatment of pathological tooth migration: interdisciplinary periodontic-orthodontic approach to the treatment of pathological tooth migration - Sulfadliana; Sri Oktawati (Makassar Dental Journal PDGI Makassar, 2024)
Pathological tooth migration (PTM) is a common disorder in chronic periodontitis. Clinical signs of PTM include labial tooth shift-ing, diastema, rotation and extrusion, resulting in aesthetic disturbance and patient visits to the dental clinic. This literature review discusses the periodontic-orthodontic treatment approach to manage PTM cases. An internet-based search was conducted to identify literature on PTM using several keywords. Orthodontic treatment can be started once the periodontal disease is controlled. Good treatment results can be achieved in patients with compromised dentofacial aesthetics. It is concluded that an interdiscipli-nary periodonti-orthodontic approach can help achieve good functional and aesthetic outcomes in malocclusion cases with per-vasive chronic periodontitis.